Product Development Through Diversification in an Effort to Increase Sales Volume - Yusuf, Daniel (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Creativity and innovation, which are part of product diversification, are essential in creating products with greater uniqueness. This is expected to help restore the existence of home industries. The purpose of this study is to determine strategies to sustain home industries through product diversification. Today, the industrial world has begun to develop, marked by increasingly advanced tools and technologies. A diversification strategy is an effort to vary product types from similar products into a wider range of variations. Thus, the variety of products available is expected to attract consumer interest and encourage them to purchase the company’s products. This research is a field research study with a descriptive nature, using qualitative analysis techniques and an inductive reasoning approach. The data sources used include primary and secondary data. Primary data were used to obtain information regarding product development through diversification in an effort to increase sales volume. Meanwhile, secondary data were used to explore various theories related to the existing problems. Based on the results of the research conducted, it can be concluded that product development through diversification to increase sales volume has been carried out as effectively as possible. The strategy implemented is a product strategy in which the company prioritizes the product aspect. Therefore, the diversification strategy policy becomes a step taken to address the decline in sales volume.